(untitled) (Research Data Journal for the Humanities and Social Sciences, 2024)
This article presents a database on film programming in Moscow cinemas between 1946 and 1955. It outlines the place of this research at the intersection of new cinema history and academic debates on film distribution in the field of Soviet history. The article describes the data collection, the coding to present the data, and the structure of the database, which consists of the three datasets on Moscow film programming (1946–1955), Moscow cinemas (1946–1955), and the 1952 film calendar. Concluding remarks summarize the knowledge obtained from the database and introduce the Soviet case into the international context of digital data collections for historical cinema studies.